Sistem Komunikasi Interpersonal: Persepsi Interpersonal, Konsep Diri, Atraksi, dan Hubungan Interpersonal - Ahmad Fauzi Zainal Abidin; Muhammad Husnan Syadiidan; Umi Halwati (MAN 4 Kota Pekanbaru, 2026)
Interpersonal communication often fails not merely because of message ambiguity, but because of psychological barriers within communicators. This study aims to examine interpersonal communication as a systemic psychological process involving four interdependent elements: interpersonal perception, self-concept, interpersonal attraction, and relationship quality. Using a qualitative literature review, the study applies content analysis and theoretical synthesis to selected scholarly works published between 2020 and 2025. The findings show that interpersonal communication operates cyclically: perception shapes self-concept, self-concept influences attraction, attraction determines interaction intensity, and these processes affect relationship quality. Disruption in one element, such as biased perception or negative self-concept, can weaken the entire relational system. This study contributes a holistic conceptual framework that explains interpersonal communication beyond message clarity by emphasizing the role of psychological integration in building effective, supportive, and adaptive interpersonal relationships.